Nature - Evdokimov, Paul (Scottish journal of theology, 1965)
The biblical narrative describes the progressive course of creation ending with man. Man appears as its culmination, as a centre on which all the planes of the world converge, a ‘microcosm’. But, ‘created in the image of God’ he is also, according to the Fathers, a ‘microtheos’. This central position of man explains the normative subjection of nature to man as to its cosmic logos, as to one of its multiple hypostases. Man ‘cultivates’ nature, gives a name to creatures and things, ‘humanises’ them. His direct relation with the Creator is constitutive of his being.